Outcomes of percutaneous transhepatic gallbladder drainage versus percutaneous transhepatic biliary drainage for obstructive jaundice - Tetsushi Azami; Yuichi Takano; Naoki Tamai; Jun Noda; Masataka Yamawaki; Fumitaka Niiya; Naotaka Maruoka; Fumiya Nishimoto; Akira Ishihara; Masatsugu Nagahama (PLoS ONE, 2025)
Percutaneous transhepatic gallbladder drainage (PTGBD) is an alternative to percutaneous transhepatic biliary drainage (PTBD) for cases with obstructive jaundice in which the bile duct obstruction is below the confluence of the cystic ducts. This retrospective study aimed to evaluate the usefulness of PTGBD and PTBD in patients with obstructive jaundice. We recruited patients who had undergone percutaneous biliary drainage for acute cholangitis and obstructive jaundice at two institutions between January 2017 and March 2024. In principle, PTBD was the first choice. PTGBD was selected for cases where the intrahepatic bile duct diameter was ≤ 5 mm or ≥ 6 mm with significant respiratory-related variability of the positioning of the bile ducts. In other cases, PTBD was chosen. Fifty-five patients were included in this analysis. However, patients with intrahepatic or hilar bile duct stenosis, post choledocholithiasis, complex cholecystitis, total bilirubin levels of < 2.0 mg/dL, and uncorrectable bleeding tendency and those who had undergone the procedure and later discontinued without puncture were excluded. The technical success rates, clinical success rates, and complication rates of the procedure were evaluated. The technical success rates were 96.3% (26/27) and 82.1% (23/28) in the PTGBD and PTBD groups, respectively. The clinical success rates were 85.2% (23/27) and 67.9% (19/28) in the PTGBD and PTBD groups, respectively. The complication rates were 18.5% (5/27) and 25.0% (7/28) in the PTGBD and PTBD groups, respectively. No serious complications were observed in either group. Hence, the two groups did not significantly differ in any of the endpoints. The outcomes of PTGBD were comparable to those of PTBD in patients with obstructive jaundice. Hence, PTGBD is a reasonable treatment option for cases of obstructive jaundice in which PTBD is not feasible.